2018
DOI: 10.31235/osf.io/4ygux
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to Opposing Views can Increase Political Polarization: Evidence from a Large-Scale Field Experiment on Social Media

Abstract: There is mounting concern that social media sites contribute to political polarization by creating "echo chambers" that insulate people from opposing views about current events. We surveyed a large sample of Democrats and Republicans who visit Twitter at least three times each week about a range of social policy issues. One week later, we randomly assigned respondents to a treatment condition in which they were offered financial incentives to follow a 1 Twitter bot for one month that exposed them to messages p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…Social media generates a more fragmented news environment, more sources with lower quality and channels for bad or fake news (Lazer et al 2018) . Social media exposes users to opposing viewpoints which can activate the boomerang effect of entrenching/reinforcing extreme positions (Bail et al 2018) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social media generates a more fragmented news environment, more sources with lower quality and channels for bad or fake news (Lazer et al 2018) . Social media exposes users to opposing viewpoints which can activate the boomerang effect of entrenching/reinforcing extreme positions (Bail et al 2018) .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond just reflecting the media environment at large however, other research has highlighted ways Twitter and other social media platforms may work to promote polarization and ultimately harm democracy (Barberá et al 2018;Sunstein 2018;Tucker et al 2018) . Research has identified three mechanisms: first, social media exposes people to uncivil conversations around contentious issues which leads to increases in affective polarization (Lelkes 2016;Suhay, Bello-Pardo, and Maurer 2018;Weeks 2015) ; second, by generating a fragmented news environment that lowers the overall quality and creates spaces for the spread of disinformation (Lazer et al 2018;Vosoughi, Roy, and Aral 2018) and incorporation of otherwise fringe views (Bail 2012;Farrell 2016a) ; third, it exposes users to larger number of opposing viewpoints which can activate the type of "boomerang" or "hostile media" response seen in general media (Bail et al 2018) .…”
Section: Social Media Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…While overtly congruent social networks are commonly associated with attitudinal polarization and increased intergroup bias (Wojcieszak & Garrett, 2018), the exposure to incongruent views is commonly linked to desirable outcomes as, for example, openness to diverging views and increases in political tolerance (Mutz, 2002a). Different from that, rather than improving the relationship between political groups, some research pointed out that the exposure to incongruent views can likewise foster polarization and selective exposure to information (Bail et al, 2018;Weeks et al, 2017). It hence appears that effects of exposure to congruent and incongruent views are contingent to further contextual variables.…”
Section: Opinion Climates On Social Networking Sites Impacts Users' Pmentioning
confidence: 99%
“…Furthermore, the exposure to incongruent views can evoke attitudinal ambivalence, i.e., the formation of simultaneously positive and negative views on one and the same issue (Huckfeldt et al, 2004;Jonas et al, 1997;Mutz, 2002b), and therefore mitigate own convictions (Schneider & Schwarz, 2017). However, exposure to incongruent views does not mitigate opinions under all circumstances (Bail et al, 2018;Kim, 2015;Weeks et al, 2017;Yardi & boyd, 2010).…”
Section: Cognitive Effects Of Congruence and Incongruence: Opinion Stmentioning
confidence: 99%